Hyphenated technique for the extraction and determination of isoflavones in algae: ultrasound-assisted supercritical fluid extraction followed by fast chromatography with tandem mass spectrometry - Klejdus, B; Lojková, L; Plaza, M; Snóblová, M; Stěrbová, D (Journal of chromatography. A, 2010)
New hyphenated technique for the extraction and determination of isoflavones in sea and freshwater algae and cyanobacteria was developed. The method consists of sonication sample pretreatment, extraction by supercritical CO(2) modified by 3% (v/v) of MeOH/H(2)O mixture (9:1, v/v) at 35 MPa and 40°C for 60 min, fast chromatography analysis by the means of Agilent 1200 Series Rapid Resolution and MS/MS determination. Agilent 1200 Series RRLC was used with Zorbax SB-CN chromatographic column (100 mm × 2.1mm, particle size 3.5 μm), 3μl injection volume, mobile phase consisting of 0.2% (v/v) acetic acid in water (solvent A) and acetonitrile (solvent B) and used with linear gradient (30% B at 0 min, from 0 min to 3 min up to 50% B, from 3 to 6 min up to 80% B and from 6 to 10 min down to 30% B). The flow-rate was 0.4 mL/min, column oven temperature 35°C. MS detector Agilent Technologies 6460 Triple quadrupole LC/MS with Agilent Jet Stream was used in a negative ESI mode under following conditions: gas temperature 350°C, gas flow 13 L/min, nebulizer gas pressure 50 psi, sheath gas temperature 400°C, sheath gas flow 12L/min, capillary voltage was 4 kV. Samples were analysed in the multiple reaction monitoring (MRM) mode. Eight isoflavone compounds were found for the first time in seven real samples of sea algae and in three control samples of freshwater algae and cyanobacteria. Usual optimisation study of extraction parameters was performed. Pressure and temperature optima for algae matrix are different from those obtained sooner for other matrices for most of the analytes, but the results of modifier optimisation study are in good accordance with those obtained sooner for spiked samples and red clover matrix. It seems that matrix has very small or no effect on the modifier selection. Two different approaches of sonication pretreatment were tested: sonication bath and the thorn instrument. In longer extraction time experiments, thorn sonication was more efficient and recovery of following supercritical fluid extraction was higher.
Keywords: superkritická fluidní chromatografie; ultrazvuk; isoflavony; tandemová hmotnostní spektrometrie; Ultrasonics; Rhodophyta; Isoflavones; Chromatography, Liquid; Tandem Mass Spectrometry; chromatografie kapalinová; Chromatography, Supercritical Fluid; Phaeophyceae